Pengaruh Partisipasi Dalam Penyusunan Anggaran, Akuntabilitas Publik Dan Job Relevant Information Terhadap Kinerja Manajerial Pada OPD Provinsi Sumatera Barat - Rani Sri Wahyuni; Erinos NR (Universitas Negeri Padang, 2019)
This studyaimed to examine the effect of budgeting participation, public accountability and job relevant information to managerial performance. This research is classified as causative research. The population in this study are 39 Regional Organizations (OPD) of West Sumatra Province. The sample in this study used the Total Sampling method. The type of data used in this study is primary and secondary data. Data collection techniques using a questionnaire consisting of 3 respondents in each OPD so that the questionnaire distributed was 117 questionnaires. The analytical method used is Multiple Regression Analysis using the SPSS version 20.00 program. The result of the study showed participation has a significant positive effect on managerial performance. However public accountability and job relevant information have no effect on managerial performance.